Analysis of rain fade duration models for Earth-to-satellite path based on data measured in Malaysia - Hassan , Dao; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed (2013)
Statistical analysis of rain fade duration is crucial information for system engineer to design and plan a fade mitigation technique (FMT) for the satellite communication system. An investigation is carried out based on data measured of one year period in Kuala Lumpur, Malaysia from satellite path of MEASAT3. This paper presents statistical analysis of measured fade duration on high elevation angle (77.4˚) in Ku-band compared to three prediction models of fade duration. It is found that none of the models could predict measured fade duration distribution accurately.